2014
DOI: 10.1111/1756-185x.12486
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between synovial fluid VEGF and serum leptin with ultrasonographic findings in knee osteoarthritis

Abstract: Synovial fluid VEGF level was correlated with radiographic grading, ultrasonographic findings and functional statues in knee osteoarthritis, and serum leptin level also correlated with the ultrasonographic findings and functional status of knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
2
16
0
2
Order By: Relevance
“…In agreement with our study Kim et al [23], they found that the level of VEGF was higher in patients with KL grade 4 than those with KL grade 2 and there was positive correlation between synovial VEGF and KL grades. In addition, Lee et al [27] who studied 34 OA patients, they found that the synovial fluid level of VEGF was higher in patients with KL grade 4 than those of KL grade 2 and synovial VEGF level was positively correlated with KL scores, however they differ from our study as they found no significant difference in plasma VEGF level among OA patients with different KL grades.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our study Kim et al [23], they found that the level of VEGF was higher in patients with KL grade 4 than those with KL grade 2 and there was positive correlation between synovial VEGF and KL grades. In addition, Lee et al [27] who studied 34 OA patients, they found that the synovial fluid level of VEGF was higher in patients with KL grade 4 than those of KL grade 2 and synovial VEGF level was positively correlated with KL scores, however they differ from our study as they found no significant difference in plasma VEGF level among OA patients with different KL grades.…”
Section: Discussionsupporting
confidence: 93%
“…Rübenhagen et al [26] detected significant correlation between the synovial fluid level of VEGF and the age of patients. On the contrary Kim et al [23] found negative correlation between synovial fluid VEGF and total WOMAC, WOMAC stiffness and WOMAC function. Also there was negative correlation between synovial VEGF and total WOMAC, WOMAC pain and WOMAC stiffness.…”
Section: Discussionmentioning
confidence: 86%
“…VEGF is a secreted mitogen associated with angiogenesis that has been reported to regulate the vascular invasion of the hypertrophic cartilage in OA; one isoform of which, VEGF-A, promotes subsequent cartilage vascularization (32,33). A meta-analysis revealed that VEGF is upregulated in patients with OA (7) and that it contributes to the severity of knee OA (34,35). Intravenous and intra-articular administration of the anti-VEGF antibody bevacizumab facilitates articular cartilage repair and attenuates the severity of OA (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is an extremely important process in normal development and tissue homeostasis and repair, besides contributes directly also to various forms of pathology, such as tumor development and metastasis, psoriasis, rheumatoid arthritis, and wet macular degeneration [37]. One of the most important proangiogenic mediators is vascular endothelial growth factor (VEGF), responsible for stimulating new blood vessels formation, tissue proliferation, migration, differentiation, and survival, which contribute to the angiogenesis process, in addition to influencing the repair and wound closure and granulation tissue formation [38]. The VEGF family has several members, and one of its members such as VEGF-A begins the process of wound healing promoting biological events linked to angiogenesis and migration of endothelial cells [39].…”
Section: Growth Factorsmentioning
confidence: 99%